Estimation and Validation of Collection 6 Moderate Resolution Imaging Spectroradiometer Aerosol Products for East Asia - Kwon-Ho Lee (Asian Journal of Atmospheric Environment, 2018)
The operational aerosol retrieval algorithm for the Moderate Resolution Imaging Spectroradiometer (MODIS) measurements was recently updated and named collection 6 (C6). The C6 MODIS aerosol algorithm, a substantially improved version of the collection 5 (C5) algorithm, uses an enhanced aerosol optical thickness (AOT) retrieval process consisting of new surface reflection and aerosol models. This study reports on the estimation and validation of the two latest versions, the C5 and C6 MODIS aerosol products over the East Asian region covering 20°N to 56°N and 80°E to 150°E. This study also presents a comparative validation of the two versions (C5 and C6) of algorithms with different methods (Dark Target (DT) and Deep Blue (DB) retrieval methods) from the Terra and Aqua platforms to make use of the Aerosol Robotic Network (AERONET) sites for the years 2000-2016. Over the study region, the spatially averaged annual mean AOT retrieved from C6 AOT is about 0.035 (5%) less than the C5 counterparts. The linear correlations between MODIS and AERONET AOT are R = 0.89 (slope = 0.86) for C5 and R = 0.95 (slope = 1.00) for C6. Moreover, the magnitude of the mean error in C6 AOT-the difference between MODIS AOT and AERONET AOT-is 40% less than that in C5 AOT.